Public Confidence in Policing : A Neo-Durkheimian Perspective - Jackson, Jonathan (The British journal of criminology, 2007)
Public confidence in policing has received much attention in recent years, but few studies outside of the United States have examined the sociological and social-psychological processes that underpin trust and support. This study, conducted in a rural English location, finds that trust and confidence in the police are shaped not by sentiments about risk and crime, but by evaluations of the values and morals that underpin community life. Furthermore, to garner public confidence, the police must be seen first to typify group morals and values and second to treat the public with dignity and fairness. All these findings are consistent with the perspective that people are Durkheimian in their attitudes towards crime, policing and punishment - a perspective developed here in this paper